The Application of UHPLC-HRMS for Quality Control of Traditional Chinese Medicine - Ma, Jieyao; Li, Kailin; Shi, Silin; Li, Jian; Tang, Sunv; Liu, LiangHong (Frontiers in Pharmacology, 2022)
Ultra-high-performance liquid chromatography-high resolution mass spectrometry (UHPLC-HRMS) is a relatively new technique that organically unifies UHPLC with HRMS. Due to the good separation ability and high sensitivity of UHPLC and the sensitivity of HRMS, this technique has been widely used for structure identification, quantitative determination, fingerprint analysis, and elucidation of the mechanisms of action of traditional Chinese medicines (TCMs) in recent years. This review mainly outlines the advantages of UHPLC-HRMS and provides a survey of the research advances of UHPLC-HRMS in the field of quality control of TCMs.